Seroprevalence of tuberculosis in domesticated elk (Cervus canadensis) in Korea. (August 2016) - Kang, Shin-Seok; Byeon, Hyeon-Seop; Ku, Bok Kyung; Kim, Sang Woo; Kim, Jiro; Woo, Jeongim; Ahn, Byeongwoo; Kim, Soojin; Monoldorova, Sezim; Park, Chan-Ho; Cho, Sang-Nae; Jeon, Bo-Young
Abstract: Tuberculosis is a contagious disease in animals, primarily cattle, although it also affects wild animals and humans. There are few data on the state of tuberculosis in domesticated elk ( Cervus canadensis ) in Korea. In order to investigate tuberculosis in elk, the effectiveness of an enzyme linked immunosorbent assay (ELISA) using MPB70 and MPB83 antigens was compared with the tuberculin skin test (TST), and seroprevalence was measured with this assay using serum samples collected from domesticated elk herds in Korea. The respective sensitivities of the MPB70 and MPB83 ELISAs were 51.9% (95% CI 42.0–61.6) and 49.1% (95% CI 39.3–58.9), and their specificities were 100.0% (95% CI 92.6–100.0) and 97.9% (95% CI 88.9–100.0), respectively, in comparison with the TST. The herd prevalence ranged from 50 to 80% and the mean herd seropositive rate was 67.7% (21 of 31). Of 819 serum samples, 163 (19.9%) were seropositive, and the within-region prevalence ranged from 18.5–58.0%. In conclusion, the ELISA using the MPB70 and MPB83 antigens showed moderate sensitivity and high specificity compared to TST in elk, and tuberculosis was assumed to be fairly prevalent in domesticated elk in Korea. Highlights: Establishment of ELISA using the MPB70 and MPB83 antigens for tuberculosis of elk Performance of these ELISAs (sensitivity and specificity) compared with TST Estimation of seroprevalence of tuberculosis in elk in Korea using these ELISAs First report on prevalence data of tuberculosis in domesticated elk in Korea A basic epidemiological data of tuberculosis in elk in an Asian region